Fusion iENA Scholar Study: Sensor-Navigated I-124-PET/US Fusion Imaging versus Conventional Diagnostics for Retrospective Functional Assessment of Thyroid Nodules by Medical Students - Martin Freesmeyer; Thomas Winkens; Luis Weissenrieder; Christian Kühnel; Falk Gühne; Simone Schenke; Robert Drescher; Philipp Seifert (Sensors, 2020)
In conventional thyroid diagnostics, the topographical correlation between thyroid nodules (TN) depicted on ultrasound (US) in axial or sagittal orientation and coronally displayed scintigraphy images can be challenging. Sensor-navigated I-124-PET/US fusion imaging has been introduced as a problem-solving tool for ambiguous cases. The purpose of this study was to investigate the results of multiple unexperienced medical students (MS) versus multiple nuclear medicine physicians (MD) regarding the overvalue of I-124-PET/US in comparison to conventional diagnostics (CD) for the functional assessment of TN. Methods: Out of clinical routine, cases with ambiguous findings on CD were selected for I-124-PET/US fusion imaging. Sixty-eight digital patient case files (PCF) of 34 patients (CDonly and CD+PET/US PCF) comprising 66 TN were provided to be retrospectively evaluated by 70 MD and 70 MS, respectively. A total of 2174 ratings (32.9 per TN) were carried out: 555 ratings (8.4 per TN) for CDonly and 532 ratings (8.1 per TN) for CD+PET/US by each MD and MS. Results: Functional assessment revealed 8.5%/11.7% (n.s.) (16.4%/25.8% (p = 0.0002)), 41.8%/28.5% (p < 0.0001) (23.9%/17.9% (p = 0.0193)), 36.0%/30.5% (n.s.) (57.3%/53.9% (n.s.)), and 13.7%/29.4% (p < 0.0001) (2.4%/2.4% (n.s.)) hyperfunctioning, indifferent, hypofunctioning, and not rateable TNs for CDonly (CD+PET/US) and MD/MS, respectively. The respective rating confidence was indicated as absolute certain, quite certain, equivocal, uncertain, and not rateable in 11.7/3.4% (p < 0.0001) (44.9%/38.9% (p = 0.0541), 51.9%/26.7% (p < 0.0001) (46.2%/41.5% (n.s.)), 21.6%/29.0% (p = 0.0051) (6.2%/14.8% (p < 0.0001)), 1.1%/11.5% (p < 0.0001) (0.2%/2.3% (p = 0.0032)), and 13.7%/29.4% (p < 0.0001) (2.4%/2.4% (n.s.)) by MD/MS, respectively. There was a significant difference in the diversity of the observers’ functional assessment of TN (MD 0.84 vs. MS 1.02, p = 0.0006) and the respective confidence in functional assessment (MD 0.93 vs. MS 1.16, p < 0.0001) between MD and MS on CDonly, whereas CD+PET/US revealed weaker differences for both groups (MD 0.48 vs. MS 0.47, p = 0.57; and MD 0.66 vs. MS 0.83, p = 0.0437). With the additional application of I-124-PET/US, the rating diversity of both MD and MS markedly tends towards more consistency (p < 0.0001 in each case). Conclusion: The additional application of sensor-navigated I-124-PET/US fusion imaging significantly influenced the functional assessment of TN positively, especially for unexperienced observers.